If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 13 + -7 + 6x = 0 Reorder the terms: 13 + -7 + 2x + 6x = 0 Combine like terms: 13 + -7 = 6 6 + 2x + 6x = 0 Combine like terms: 2x + 6x = 8x 6 + 8x = 0 Solving 6 + 8x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 8x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + 8x = 0 + -6 8x = 0 + -6 Combine like terms: 0 + -6 = -6 8x = -6 Divide each side by '8'. x = -0.75 Simplifying x = -0.75
| -16=-3(6k+9) | | 23=2+8(r+5) | | -20=-9d-2d | | 4.2+7=2.8 | | 3p^2+24p=-105 | | 6x^2-13b=0 | | 3-3*6+3=-13 | | -6+8(1-2x)=27 | | 9y+8+7=-26 | | (x+5)2=(2x)2 | | -6x-6=7x+33 | | 4(3y+2)=-28 | | -.4x+25=0 | | 3y=155-2x | | 1-3y=3-4y | | 4w-3w+4=-4+7 | | 13x+72= | | a-12+5=-12 | | 6-9n+5n=16-90 | | 9*x=88 | | x+45=6x | | 3(c-2)+8=6+c-4 | | 3x+1=3x+0 | | 2x+3y=155 | | 9.8.2x=96 | | 2z-6z=-25 | | 20=22-d | | -7(9-5a)=-23 | | 3p.9=24 | | -4+3(18-9m)= | | x(x+4)+28=(x-1)(x+8) | | 5=6p-1 |